Orthostatic hypotension as an unusual presentation of spinal calcium pyrophosphate deposition disease: case report and review of literature - De Azevedo Sofia Moura; Pichel Rita Carrilho; Freitas Egídio; Campar Ana; Marinho António; Mendonça Teresa (Romanian Journal of Internal Medicine, 2023)
Calcium pyrophosphate crystal deposition disease (CPPD), also known as pseudogout, with spinal involvement, is associated with clinical manifestations of acute nerve compression or chronic spinal stenosis. Precipitation of crystals of calcium pyrophosphate dihydrate in connective tissues can lead to acute inflammatory arthritis, degenerative chronic arthropathies, and radiographic evidence of cartilage calcification.